Three‐Year‐Olds' Reactions to a Partner's Failure to Perform Her Role in a Joint Commitment. Issue 5 (15th May 2017) - Kachel, Ulrike; Svetlova, Margarita; Tomasello, Michael
Abstract : When children make a joint commitment to collaborate, obligations are created. Pairs of 3‐year‐old children ( N  = 144) made a joint commitment to play a game. In three different conditions the game was interrupted in the middle either because: (a) the partner child intentionally defected, (b) the partner child was ignorant about how to play, or (c) the apparatus broke. The subject child reacted differently in the three cases, protesting normatively against defection (with emotional arousal and later tattling), teaching when the partner seemed to be ignorant, or simply blaming the apparatus when it broke. These results suggest that 3‐year‐old children are competent in making appropriate normative evaluations of intentions and obligations of collaborative partners.